Potential running related injury contributors in South African long-distance runners - JÃ¤ger, Chloë Rose Laubscher (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Running related injuries (RRIs) are a common problem among long-distance runners, with injury rates ranging from 19.4% to 79.3%. Many studies have been done, investigating possible contributors to RRIs however, very few studies have investigated RRIs in South African long-distance runners, a population which may differ from previously studied populations. The current study aimed to build a descriptive profile of South African long-distance runners, as well as to determine associated factors that may contribute to RRIs. In order to do this, a cross-sectional, retrospective study design was employed using a questionnaire which was mostly electronically distributed. The sample consisted of 378 long-distance runners from each province in South Africa (SA). Using the Chi-square analysis and Fisher exact tests, significant associations were established (p<0.05). The current study found that certain RRI variables were associated with specific aspects of the participants' personal characteristics and demographics, training characteristics, running experience, footwear, and cross training activities. Footwear and training characteristics produced the largest number of significant RRI associations. The findings of the current study could assist future research on RRIs in South African long-distance runners, by informing researchers of potential areas where more in-depth research is needed. In the long term, researchers may be able to narrow down the main contributors to RRI, possibly decreasing RRI rates in the unique population of South African long-distance runners.
Keywords: Running injuries -- South Africa; Long-distance running -- South Africa; Running Physiological aspects; Running shoes; Biomechanics; Chi-square test; Fisher exact test